Sociodemography and Clinical Profile of COVID 19 Positive Physicians at a Tertiary Level Hospital, Dhaka - Islam, Mohammad Rafiqul; Bashar, Khondaker Abul; Matin, Shariful; Tanveer, Tahmid; Rahman, Atiqur; Mowla, Syed Ghulam Mogni; Murshed, KM Mamun; Barua, Uttam Kumar (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: On 11th March, 2020 COVID19 was declared as a pandemic and it currently involves 210 countries worldwide. Bangladesh declared its first case on 8th March 2020. Currently, the highest case detection of COVID is in the Dhaka district. Due to a lack of quality PPE (personal protection equipment) and proper knowledge of donning, doffing and transmission dynamics of COVID 19 thought to be high infection rate among physicians. Material and Methods: A pretested questionnaire was set and distributed among COVID 19 infected physicians working at Shaheed Suhrawardy Medical College Hospital through internet to know about the clinical and epidemiological characteristics. Results: 65.3% of the respondents were male and had a mean age were 35.7 years. Among all the respondents, the highest number of physicians involved were from medicine department (26.9%). Lethargy, body ache and fever were observed in 57.69%, 50% and 30.7% patients respectively. Among 52 infected physicians, first time RT-PCR for COVID 19 yield 78.8% positive results. Prophylactic dose of hydroxychloroquine taken by 15.3% patients before being infected with COVID19. Conclusion: Health care workers are getting infected in a alarming number but fortunately at Shaheed Suhrawardy Medical college all the cases were in mild form. J Bangladesh Coll Phys Surg 2020; 38(0): 56-60